Pemikiran Tentang Pengembangan Layanan Khusus Siswa Cerdas Istimewa (CI) Dan Berbakat Istimewa (BI) Di Madrasah Aliyah Negeri 2 Ponorogo - Hamdy, Mohammad Zainal; Ningsih, Wiwik Prasetiyo; Huda, Miftahul (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
Specially Intelligent and Specially Talented are extraordinary human resource potentials that must be empowered and maximized. One way to optimize this potential is to provide special class services that suit their needs for school-age children. Madrasah Aliyah Negeri 2 Ponorogo is one of the schools that has special services for Specially Intelligent and Specially Talented students. The purpose of this study was to understand about Specially Intelligent and Specially Talented Students, and to find out what special services MAN 2 Ponorogo has for Specially Intelligent and Specially Talented Students. This study uses a Qualitative Field Type Approach where data is generated through Interviews, Documentation, and Documents. The results of this study are that Specially Intelligent and Specially Talented students are students who have above average intelligence, marked by an IQ above 130, are able to learn quickly, and are able to think abstractly and complexly. Meanwhile, the class services available at MAN 2 Ponorogo for Specially Intelligent and Specially Talented Students are the 2-year Semester Credit System (SKS) Class, Achievement Development Class, Skills Class, Sports Class, Research Class, Tahfidz Class, Olympiad Class, and Academic Class.